A Straightforward and High-Yielding Synthesis of 1,2,4-Oxadiazoles from Chiral N-Protected α-Amino Acids and Amidoximes in Acetone-Water: An Eco-Friendly Approach - André C. Sauer; Lucas Wolf; Natália Quoos; Mariele B. Rodrigues; Antônio L. Braga; Oscar E. D. Rodrigues; Luciano Dornelles (Journal of Chemistry)
A straightforward and high-yielding methodology for the synthesis of a high structural diversity of 1,2,4-oxadiazoles from different chiral N-protected α-amino acids and amidoximes under microwave (MW) irradiation is described herein. This greener approach gives the desired products using acetone/water as solvent in very short reaction times.